THE URGENCY OF SOCIAL SUPPORT AS THE PREVENTION OF LOST TO FOLLOW-UP (LTFU) STRATEGY ON PEOPLE LIVING WITH HIV/AIDS (PLWHA) IN GARUT REGENCY, WEST JAVA, INDONESIA - Deswanti, Arini Dwi; Sutisna, Nono; Hakim, Moch Zaenal (Indonesian Journal of Social Work, 2024)
The social support received by people living with HIV/AIDS (PLWHA) plays a very important role in increasing their self-confidence and meaning of life and enabling them to continue their lives. The purpose of this study is to describe the social support received by PLWHA in Garut Regency as a strategy that can be used to prevent lost of follow-up antiretroviral therapy for PLWHA. This study uses a qualitative descriptive method. The informant selection technique in this study used purposive sampling, with the number of informants obtained reaching as many as 10 people. Data collection in this study was obtained from in-depth interviews, observation, and documentation studies. The location of this research was Garut Regency. The study results indicate that LTFU is a big challenge for PLWHA. First, the side effects that are caused by PLWHA make PLWHA feel uncomfortable. PLWHA prefer to stop taking medication because they are unable to overcome the side effects of ARV therapy. Second, the stigma and discrimination attached to PLWHA also make them lazy to continue their treatment because they are embarrassed and do not want to get stigma and discrimination, which makes PLWHA choose to stop their treatment. Social support, especially from family members, played a major role in PLWHA's being able to consistently undergo ARV therapy. The family member who knows about PLWHA's condition helps remind PLWHA to always take medication and check their health condition routinely at the hospital. In addition, social support from NGOs also plays an important role in helping PLWHA get access to affordable or free health services. Social support from buddies at NGOs who are also HIV-positive turned out to be very helpful for PLWHA in accepting their condition as HIV-positive people. It can be concluded that social support strengthens PLWHA to be able to continue their lives with more confidence, meaning, and stronger personalities in the middle of a society that still gives stigma and discrimination to PLWHA.